The Decrasing Trend of Precipitation Observed at Watersheds in Padang for The Period 1975-2013 - Wilis, Ratna; Nugroho, Sugeng (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
One of the consequences of the ongoing climate change is the increasing likelihood of extreme precipitation frequency in the future, which causes the declining trend of total precipitation that affects water debits in the watersheds and brings difficulties to a city like Padang that is situated near the watersheds. In order to elaborate on this, a number of extreme precipitation indices recommended by ETCCDMI was utilized to assess the extreme precipitation condition for the period 1975-2013. These indices were calculated based on the rain-gauge stations along the watersheds in and around Padang. Before processing the data, a series of homogeneity test were undertaken to make sure the data were comparable. The results showed that there was a significant declining trend on the total annual precipitation (PRCPTOT), an increasing trend of the number of days without rain (R0) and a decreasing frequency of the number of days with precipitation of more than 50 mm in the Batang Kuranji Watershed. The results suggested that atmospheric circulations, such as El Nino and positive Dipole Mode, have played their role on the trend as a result of their intensified frequency due to global warming.